2011
DOI: 10.1002/aic.12589
|View full text |Cite
|
Sign up to set email alerts
|

Detailed kinetic analysis of oil shale pyrolysis TGA data

Abstract: There are significant resources of oil shale in the western United States, which if exploited in an environmentally responsible manner would provide secure access to transportation fuels. Understanding the kinetics of kerogen decomposition to oil is critical to designing a viable process. A dataset of thermogravimetric analysis (TGA) of the Green River oil shale is provided and two distinct data analysis approachesadvanced isoconversional method and parameter fitting are used to analyze the data. Activation en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(63 citation statements)
references
References 62 publications
3
60
0
Order By: Relevance
“…1b). The first weight-loss region around $250-500°C is dominated by the desired pyrolysis of kerogen [31]. The second weight-loss region located above 650°C is dominated mainly by the decomposition of carbonates such as calcite in the [31,18].…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…1b). The first weight-loss region around $250-500°C is dominated by the desired pyrolysis of kerogen [31]. The second weight-loss region located above 650°C is dominated mainly by the decomposition of carbonates such as calcite in the [31,18].…”
Section: Methodsmentioning
confidence: 98%
“…Note: the Q Ads value for OS ash is the value for the ash prepared by per gram of raw OS, and thus the unit (J g À1 K À1 ) of the Q Ads for OS ash in the figure is also joules per gram of raw OS per Kelvin. non-isothermal mode, the decomposition of kerogen could be represented by the following reaction [31]:…”
Section: Reaction Kinetics Of Kerogen Decomposition In Different Procmentioning
confidence: 99%
“…Capillary gases may be oxidizing, inert, or reducing. An oxidizing atmosphere, such as air or oxygen, combusts organic materials and oxidizes metals . Changing oxidation states complicates the analysis as the mass increases.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, heating rate is a significant factor and should not be more than 10.0 or 20.0°C/min to get a stable and informative TG plot . On the other hand, the flow rate of nitrogen gas was set at 50 mL/min which is often recommended for oil shale . As indicated in Figure , typical TG plots were reported which confirmed that serious composition of organic matter started at temperatures higher than 400°C at both flow rates.…”
Section: Resultsmentioning
confidence: 99%